RANCANG BANGUN SISTEM BROADCAST INFORMASI PADA FAKULTAS TEKNIK UNIVERSITAS TANJUNGPURA - Agustino, Nikko (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Information is a data collection which have specific function and purpose for its receiver. Information has high urgency level to be delivered immediately to its receiver. This urgency level to deliver information also applied in college society Engineering Faculty of Tanjungpura University. Lecturers and students mobility outside university could interfere important information to be delivered via information board. Mobile devices was a right media to deliver information. For those reason, an integrated information  broadcasting  system which consists website, android application, email and SMS was developed.  Web based system will synchronize with user’s android devices. If user doesn’t have android device or not synchronized to web server for a specific time, system will send information by email and user will also receive notification SMS. From test result there was a conclusion that this information broadcasting system has really good result  to be implemented inside Engineering Faculty of Tanjungpura University environment.